Phytoconstituent-Loaded Nanofibrous Meshes as Wound Dressings: A Concise Review - Ameya Sharma; Divya Dheer; Inderbir Singh; Vivek Puri; Pradeep Kumar (Pharmaceutics, 2023)
In the past, wounds were treated with natural materials, but modern wound dressings include functional elements to expedite the process of healing and to improve skin recovery. Due to their exceptional properties, nanofibrous wound dressings are now the most cutting-edge and desirable option. Similar in structure to the skin’s own extracellular matrix (ECM), these dressings can promote tissue regeneration, wound fluid transportation, and air ductility for cellular proliferation and regeneration owing to their nanostructured fibrous meshes or scaffolds. Many academic search engines and databases, such as Google Scholar, PubMed, and Sciencedirect, were used to conduct a comprehensive evaluation of the literature for the purposes of this investigation. Using the term “nanofibrous meshes” as a keyword, this paper focuses on the importance of phytoconstituents. This review article summarizes the most recent developments and conclusions from studies on bioactive nanofibrous wound dressings infused with medicinal plants. Several wound-healing methods, wound-dressing materials, and wound-healing components derived from medicinal plants were also discussed.